2013
DOI: 10.1111/jon.12049
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐Based Morphometry of Disproportionate Cerebrospinal Fluid Space Distribution for the Differential Diagnosis of Idiopathic Normal Pressure Hydrocephalus

Abstract: The VBM-based CSF space analysis can detect disproportionate changes in CSF space and differentiate iNPH patients from those with AD or PD and healthy elderlies accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…Some researchers attributed decreased intracranial compliance to the increased flow in ventricular. 18 In this occasion, brain expansion toward the ventricles more than normal and increased the intracranial pulse pressure, causing a hyperdynamic CSF flow in aqueduct both in systole and diastole. 16 The relatively specific intracranial CSF distribution supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers attributed decreased intracranial compliance to the increased flow in ventricular. 18 In this occasion, brain expansion toward the ventricles more than normal and increased the intracranial pulse pressure, causing a hyperdynamic CSF flow in aqueduct both in systole and diastole. 16 The relatively specific intracranial CSF distribution supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…16 The relatively specific intracranial CSF distribution supports this hypothesis. 18 In this occasion, brain expansion toward the ventricles more than normal and increased the intracranial pulse pressure, causing a hyperdynamic CSF flow in aqueduct both in systole and diastole.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a multicenter randomized trial showed significantly higher improvement rates after CSF shunting in patients with DESH accompanied by one or more symptoms of the triad [6]. Furthermore, the value of DESH in differentiating iNPH from other neurologic diseases such as brain atrophy and AD has been confirmed by several studies [7,8]. Hence, DESH appears to be a predictive and diagnostic neuroimaging biomarker of iNPH.…”
mentioning
confidence: 89%
“…26 The value of DESH in differentiating iNPH from other neurologic diseases has been confirmed by several studies. [27][28][29][30] Several diagnostic criteria for iNPH have recently been proposed. 1,8 One recent study reported that the effectiveness of shunt surgery for patients who were diagnosed according to one of these guidelines remained at 62.7% in terms of the mRS. 31 The incorporation of neuroimaging features that are predictive of surgical outcomes into the diagnostic criteria would thus improve the efficacy of shunt surgery.…”
Section: Discussionmentioning
confidence: 99%